A Practical Guide for Collective Action against Corruption - Compact, UN Global (UN Global Compact, 2015)
All anti-corruption professionals looking to better understand the rel ationship between collective action and corruption should refer to the se two comprehensive guides that the UN Global Compact published. The 2015 guide has modules that cover theoretical concepts, practical reco mmendations for undertaking CA initiatives, and multiple in-depth case studies of CA projects around the world.